2002
DOI: 10.1046/j.1525-1446.2003.20107.x
|View full text |Cite
|
Sign up to set email alerts
|

Definition and Identification of Child Abuse by Finnish Public Health Nurses

Abstract: The purpose of this study was to determine how public health nurses in Finland defined child abuse and how they assessed their capability to identify child abuse in the family. Public health nurses described child abuse as consisting of physical and emotional abuse. They described physical abuse as consisting of two categories, direct physical abuse towards children and other acts causing children physical harm. Emotional abuse included neglect, teasing the child, frightening the child, rejecting the child in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 23 publications
3
25
0
4
Order By: Relevance
“…These include use of known risk factors (Appleton et al 2004), knowledge of local norms, direct observations of behaviour, reflection on the relationship between the parent and health visitor, as well as more intuitive reactions (Appleton 1994a;King et al 1997;Paavilainen & Tarkka 2003). In many cases understanding difficulties in parent-child relationships involved piecing together a jigsaw over a considerable period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include use of known risk factors (Appleton et al 2004), knowledge of local norms, direct observations of behaviour, reflection on the relationship between the parent and health visitor, as well as more intuitive reactions (Appleton 1994a;King et al 1997;Paavilainen & Tarkka 2003). In many cases understanding difficulties in parent-child relationships involved piecing together a jigsaw over a considerable period.…”
Section: Discussionmentioning
confidence: 99%
“…As well as checklists and guidelines (Appleton et al 2004), HVs utilise their 'intuitive' responses (King et al 1997;Paavilainen & Tarkka 2003) and other types of 'professional judgement' (Appleton et al 2004). While this approach may be sensitive, there are potential dangers in uncritical use of such 'internal models,' particularly in terms of culturally sensitive practice.…”
Section: Discussionmentioning
confidence: 99%
“…Shulman's (1991) work, for example, although dated, was acknowledged as infl uential by Trotter (2002) and encompassed a range of interpersonal skills, such as putting a client's feelings into words, using empathy and confrontation, clarifying the practitioner role and supporting clients in what he described as 'taboo areas'. Finally, the most recent study out of the six came from Finland, where Paavilainen and Tarkka (2003) determined how public health nurses recognise child abuse. Using focused interviews with 20 nurses, they found that nurses described their use of interactive skills, knowledge acquisition skills and problem management skills.…”
Section: The Initial Findings-and the Challengesmentioning
confidence: 99%
“…Public child healthcare nurses and doctors may observe signs of child abuse in the child’s behavior and appearance and in the family’s behavior, but they will also rely on knowledge acquisition from outside third parties [35]. Their contacts with the child and his/her parents are brief and infrequent.…”
Section: Introductionmentioning
confidence: 99%